2019
DOI: 10.3390/atmos10050259
|View full text |Cite
|
Sign up to set email alerts
|

The South Atlantic–South Indian Ocean Pattern: a Zonally Oriented Teleconnection along the Southern Hemisphere Westerly Jet in Austral Summer

Abstract: Extratropical teleconnections significantly affect the climate in subtropical and mid-latitude regions. Understanding the variability of atmospheric teleconnection in the Southern Hemisphere, however, is still limited in contrast with the well-documented counterpart in the Northern Hemisphere. This study investigates the interannual variability of mid-latitude circulation in the Southern Hemisphere in austral summer based on the ERA-Interim reanalysis dataset during 1980–2016. A stationary mid-latitude telecon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…At the same time, SST response to the atmosphere is found to be of a wavenumber-3 type in a global view 16 , 25 , 26 . Recently, it is reported that tropical Rossby waves have the potential to generate a zonal W4 pattern in the southern Indo-Atlantic Ocean basin that affects precipitation over Australia 27 .…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, SST response to the atmosphere is found to be of a wavenumber-3 type in a global view 16 , 25 , 26 . Recently, it is reported that tropical Rossby waves have the potential to generate a zonal W4 pattern in the southern Indo-Atlantic Ocean basin that affects precipitation over Australia 27 .…”
Section: Introductionmentioning
confidence: 99%
“…The correlations between EP El Niño events, represented by a positive EP index, and AUMR are weak and insignificant over northern Australia (Figure 5a, red circles). The large spread of precipitation anomalies associated with the positive EP index suggests that other factors are more influential on precipitation over northern Australia, for example, local SSTa, as observed in austral spring (Van Rensch et al, 2015, 2019. Nonlinearity in the relationship is linked to large-scale shifts in rainfall patterns, and a weak decrease in AUMR during El Niño events (Chung & Power, 2017).…”
Section: Eastern Pacific El Niñomentioning
confidence: 97%
“…It is associated with ascending motion and a negative surface temperature anomaly in the eastern Indian Ocean as well as convergence in the lower troposphere and strengthened westerly winds towards NW Australia (Lin, 2019). It has been suggested that the pattern may be caused by internal, interannual atmospheric variability that is related to zonal shifts of the South Atlantic Convergence Zone and is only weakly related to tropical Atlantic SSTs (Lin, 2019), highlighting the uncertainty about it. Further research is required to clarify the causes of the pattern, its associated variability, long‐term changes and impacts on AUMR.…”
Section: Aumr: Decadal Variability and Trendsmentioning
confidence: 99%
“…The second mode reflects a distinct wavenumber-4 pattern in the Southern Ocean (e.g., Wang and Dommenget 2016;Lin 2019), with high amplitude in the Atlantic sector. As Fig.…”
Section: Spatiotemporal Variability Modes Of Q Netmentioning
confidence: 99%